Penerapan React JS Untuk Pengembangan Frontend Pada Aplikasi Jasa Layanan Perbaikan Barang Elektronik - Tatas Buana; Yeremia Alfa Susetyo (IDEALIS : InDonEsiA journaL Information System, 2026)
Electronic device repair services still commonly use manual booking processes, such as visiting the service location directly or communicating through WhatsApp. Based on the observation results, the service process is still carried out manually, and system testing was simulated using 5 service types, 10 user accounts, and 20 dummy order data. This condition causes ineffective communication, customer queues, and limited information regarding repair status and cost estimates. Based on these problems, this study aims to implement React JS in the frontend development of an electronic device repair service application. The system development used the Waterfall method, which includes requirement, system design, implementation, testing, and maintenance. The application was developed using React JS with the support of React Router DOM, React Hooks, Fetch API, Tailwind CSS, and PostgreSQL as the database. The system produces 10 user features and 8 admin features. Functional testing using Black Box Testing on 15 scenarios showed that all system functions worked according to the specified requirements with a success rate of 100%, while User Acceptance Testing (UAT) obtained a user acceptance rate of 86.40%. The main contribution of this study is the implementation of React JS to build a component-based frontend interface that supports navigation management, Single Page Application (SPA), state management, and structured user interaction in the repair service system.